2002
DOI: 10.1254/jjp.88.451
|View full text |Cite
|
Sign up to set email alerts
|

Dipeptidyl Peptidase IV Inhibitor NVP-DPP728 Ameliorates Early Insulin Response and Glucose Tolerance in Aged Rats but Not in Aged Fischer 344 Rats Lacking Its Enzyme Activity

Abstract: ABSTRACT-The aim of this study was to investigate the effects of aging on glucose metabolism after oral glucose challenge in aged dipeptidyl peptidase IV (DPP-IV) positive (+) Fischer 344 (F344), DPP-IV deficient (-) F344 and DPP-IV(+) Wistar rats and to determine the effect of a DPP-IV inhibitor NVP-DPP728 (1-{2-[(5-cyanopyridin-2-yl)amino]ethylamino}acetyl-2-cyano-(S)-pyrrolidine monohydrochloride salt) on glucose tolerance in aged rats. Aging caused a decrease in early insulin response after an oral glucose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 29 publications
2
9
0
Order By: Relevance
“…These findings agree with earlier studies using other DPP-4 inhibitors in glucose-intolerant rodents, including Zucker fatty rats (Balkan et al, 1999), high-fat-fed rats (Mitani et al, 2002a), and mice (Ahrén et al, 2000), and aged rats (Mitani et al, 2002b). Our observations go further than others in that we prove the effect up to 24 h after administration of BI 1356.…”
Section: Discussionsupporting
confidence: 93%
“…These findings agree with earlier studies using other DPP-4 inhibitors in glucose-intolerant rodents, including Zucker fatty rats (Balkan et al, 1999), high-fat-fed rats (Mitani et al, 2002a), and mice (Ahrén et al, 2000), and aged rats (Mitani et al, 2002b). Our observations go further than others in that we prove the effect up to 24 h after administration of BI 1356.…”
Section: Discussionsupporting
confidence: 93%
“…The minimum effective dose of vildagliptin to inhibit DPP-4, to augment intact GLP-1, to improve ␤-cell function, and to reduce glucose excursions was 0.3 mg/kg, and a dose of 3 mg/kg exerted maximal effects on all parameters. These findings are consistent with those of several earlier studies using other DPP-4 inhibitors in glucose intolerant rodents, including Zucker fatty rats (Pederson et al, 1998;Balkan et al, 1999), high-fat-fed rats (Mitani et al, 2002a) and mice (Ahrén et al, 2000), and aged rats (Mitani et al, 2002b), although no previous studies reported on the dose-response characteristics of DPP-4 inhibitors.…”
Section: Discussionsupporting
confidence: 92%
“…Verification that DPP-4 was the dominant molecular target for the glucose lowering properties of NVP-DPP728 was illustrated in studies demonstrating that this compound acutely lowered blood glucose following oral glucose challenge in wild-type Wistar rats but not in Fischer 344 rats with an inactivating mutation in the DPP-4 gene (27). Nevertheless, DPP-4 inhibition is not capable of exerting significant antidiabetic actions in all preclinical models, as acute VP administration increased plasma levels of intact GLP-1 in older db/db mice but VP did not lower blood glucose in 24-week-old severely hyperglycemic (fasting blood glucose 29 mmol/l) db/db mice (28).…”
Section: Dpp-4 Inhibitors Lowermentioning
confidence: 99%